2018
DOI: 10.1080/09286586.2018.1481984
|View full text |Cite
|
Sign up to set email alerts
|

Impact Survey Results after SAFE Strategy Implementation in 15 Local Government Areas of Kebbi, Sokoto and Zamfara States, Nigeria

Abstract: Purpose: To determine prevalence of trachoma after interventions in 15 local government areas (LGAs) of Kebbi, Sokoto and Zamfara States, Nigeria. Methods: A population-based impact survey was conducted in each LGA using Global Trachoma Mapping Project (GTMP) protocols. In each LGA, 25 villages were selected, except in Arewa LGA, where we selected 25 villages from each of four subunits to obtain finer-resolution prevalence information. Villages were selected with probability proportional to size. In each villa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Extensive searches around Faisalabad for trachomaendemic localities in which to undertake field-based grader training and testing resulted in very few cases of active trachoma being identified, and it was resolved instead to undertake this process in Sokoto, Nigeria, where a number of local government areas still had TF prevalences of 5.0-9.9%. 30 In August 2015, a total of 23 grader trainees went to Sokoto; 16 passed the intergrader agreement tests and were certified to participate in the surveys. 28 Three recorder trainers were also trained in Sokoto; they later conducted workshops in Pakistan to train 26 recorders.…”
Section: Field Team Structure and Trainingmentioning
confidence: 99%
“…Extensive searches around Faisalabad for trachomaendemic localities in which to undertake field-based grader training and testing resulted in very few cases of active trachoma being identified, and it was resolved instead to undertake this process in Sokoto, Nigeria, where a number of local government areas still had TF prevalences of 5.0-9.9%. 30 In August 2015, a total of 23 grader trainees went to Sokoto; 16 passed the intergrader agreement tests and were certified to participate in the surveys. 28 Three recorder trainers were also trained in Sokoto; they later conducted workshops in Pakistan to train 26 recorders.…”
Section: Field Team Structure and Trainingmentioning
confidence: 99%
“…The intervention strategy for trachoma is the World Health Organization (WHO)-endorsed SAFE strategy (S: Surgery for trachomatous trichiasis (TT); A: Antibiotics to clear Ct infection; F: Facial cleanliness and E: Environmental improvement to reduce transmission of Ct ) [2,3]. Successful implementation of this strategy has resulted in a reduction in trachoma prevalence across many endemic countries [47]. WHO has set a goal of global elimination of trachoma as a public health problem by 2020 [8].…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown no significant difference in clinical outcomes between nurses and doctors [10]. These surgical efforts have seen the prevalence of trichiasis decrease significantly across several states in Nigeria [7].…”
Section: Review Surgerymentioning
confidence: 99%
“…Additionally, they have worked in close collaboration with non-governmental organisations (NGOs) and pharmaceutical companies to provide healthcare to those with, and at risk of, trachoma. However, despite great strides in reducing the incidence and prevalence of trachoma, Nigeria has been unable to achieve eradication by 2020 [7].…”
Section: Introductionmentioning
confidence: 99%